Improvisational approaches to supervision dialogue - Bjerstedt, Sven (Högre utbildning, 2017)
The reflective processes in which supervisors and doctoral students indulge together may be improvisatory to an important extent. Based on literature review and a small interview study, I argue that there are important similarities between musical improvisation and supervision dialogue regarding, for instance, the need for structure as well as continuous impulse fluidity and the need for receptivity as well as initiative. In musical improvisation as well as in supervision, it is crucial to be able to relate simultaneously, by way of qualities such as openness, wholeness, and listening, to both internal and external impulses, to both structural and communicative aspects, and to both one’s own individuality and the tradition in which one is situated. In the concluding discussion, I identify a number of implications for the education of doctoral supervisors.